2008
DOI: 10.1177/1363460708094269
|View full text |Cite
|
Sign up to set email alerts
|

Coming to an Asexual Identity: Negotiating Identity, Negotiating Desire

Abstract: Sexuality is generally considered an important aspect of self-hood. Therefore, individuals who do not experience sexual attraction, and embrace an asexual identity are in a unique position to inform the social construction of sexuality. This study explores the experiences of asexual individuals utilizing open ended Internet survey data from 102 self-identified asexual people. In this paper I describe several distinct aspects of asexual identities: the meanings of sexual, and therefore, asexual behaviors, essen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
221
0
14

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(245 citation statements)
references
References 17 publications
10
221
0
14
Order By: Relevance
“…While previous studies suggested that asexuals have generally positive attitudes toward romance (Scherrer, 2008;Van Houdenhove et al, 2015b), they did not compare attitudes held by asexual individuals with those of a control group. This may have resulted in the unsubstantiated assumption that asexuals hold similarly positive attitudes toward romance as the general population, when in fact, this study suggests they do hold positive attitudes, though not to the same extent as the general population.…”
Section: Explicit Attitudesmentioning
confidence: 94%
See 3 more Smart Citations
“…While previous studies suggested that asexuals have generally positive attitudes toward romance (Scherrer, 2008;Van Houdenhove et al, 2015b), they did not compare attitudes held by asexual individuals with those of a control group. This may have resulted in the unsubstantiated assumption that asexuals hold similarly positive attitudes toward romance as the general population, when in fact, this study suggests they do hold positive attitudes, though not to the same extent as the general population.…”
Section: Explicit Attitudesmentioning
confidence: 94%
“…Romantic asexuals, who make up the majority (Miller, 2011;Scherrer, 2008), experience similar romantic desires and needs as romantic sexual individuals, with many describing their ideal relationship as being similar to a ÔtypicalÕ sexual relationship, though without sex (Scherrer, 2008;Van Houdenhove et al, 2015b). Reports suggest that the majority of asexual participants experience romantic attraction (Gupta, 2016;Van Houdenhove et al, 2015a), with up to 79% reporting that they had experienced romantic attraction to others (Van Houdenhove et al, 2015a), and 44% reporting having been in long-term cohabiting or marital relationships (Bogaert, 2004).…”
Section: Attitudes Toward Romancementioning
confidence: 99%
See 2 more Smart Citations
“…The legitimation of each new identity engenders others. Thus, the old gay center on campus morphs into the lesbian and gay center, and then the LGB center, and then the LGBT center, and then the LGBTQ center, and at some point the LGBTQI center, and now even the LGBTQQIAAP center (lesbian, gay, bisexual, transgendered, queer, questioning, intersex, asexual, allies, and pansexual) (Davis & Kennedy 1986, Grabham 2007, Hines 2009, Monro 2003, Scherrer 2008.…”
mentioning
confidence: 99%